The Yale Center for Biomedical Innovation and Technology (CBIT): One Model to Accelerate Impact From Academic Health Care Innovation. (April 2019) - Siefert, Alyssa L.; Cartiera, Malgorzata S.; Khalid, Ayesha N.; Nantel, Michelle C.; Loose, Christopher R.; Schulam, Peter G.; Saltzman, W. Mark; Dempsey, Michael K.
Abstract : The process of translating academic biomedical advances into clinical care improvements is difficult, risky, expensive, and poorly understood. Notably, many clinicians who identify health care problems do not have the time or expertise to solve the problems, and many academic researchers are unaware of important gaps in clinical care to which their expertise may apply. Recognizing an opportunity to connect people who can identify health care problems with those who can solve them, the Yale Center for Biomedical Innovation and Technology (CBIT) was established in 2014 to educate and enhance the impact of health care innovators. The authors review other health care innovation centers and describe best practices borrowed by Yale CBIT, which tailored its activities and approach to its unique ecosystem. In four years, Yale CBIT has affected over 3, 000 people and established a health care innovation cycle as an efficient strategy to guide translational research. Yale CBIT has created or supported graduate and undergraduate courses, clinical immersion programs for industry partners, and large health care hackathon events. Over 200 projects have been submitted to CBIT for mentorship, and some of those projects have been commercialized and raised millions of dollars of follow-on funding. The authors present Yale CBIT as one model of accelerating the impact of academic medicine on clinical practice and outcomes. The project advising strategy is intended to be a template to maximize the efficiency of biomedical innovation and ultimately improve the outcomes and experiences of future patients.